Examining the Effectiveness of 3D Virtual Reality Training on Problem-solving, Self-efficacy, and Teamwork Among Inexperienced Volunteers Helping With Drug Use Prevention: Randomized Controlled Trial - Chih-Huei Chiang; Chiu-Mieh Huang; Jiunn-Jye Sheu; Jung-Yu Liao; Hsiao-Pei Hsu; Shih-Wen Wang; Jong-Long Guo (JMIR Publications, 2021)
BackgroundIllegal drug usage among adolescents is a critical health problem. The Taiwanese government provides an accompanying volunteer program to prevent students who experiment with drugs from reusing them. An appropriate training program can improve volunteers' abilities to assist students using drugs. Problem-solving, self-efficacy, and teamwork are critical abilities for inexperienced volunteers who help with drug use prevention. By interacting with the animation or 3D virtual reality (VR) in the virtual scene, learners can immerse themselves in the virtual environment to learn, and 3D VR can increase learning opportunities and reduce the cost of human and material resources. ObjectiveThe aim of this study was to examine the effectiveness of spherical video-based virtual reality (SVVR) training in improving problem-solving, self-efficacy, and teamwork among volunteers who helped prevent adolescents from using illegal drugs. MethodsThis study used a randomized controlled design with a total of 68 participants in the experimental (n=35) and control (n=33) groups. The participants in the experimental group received the SVVR training program and their counterparts in the control group did not receive any training. ResultsGeneralized estimating equation analyses indicated that the experimental group showed significant posttraining improvements in problem-solving and self-efficacy but not teamwork when compared with the control group. ConclusionsThe results of this study revealed that SVVR could improve participants' problem-solving skills and self-efficacy for assisting students in not using illegal drugs. However, future studies are suggested to develop effective SVVR to assist inexperienced volunteers in enhancing their teamwork abilities. We believed that introducing the training program to more sites can enhance volunteer training so that volunteers can have a better companionship effect when helping students quit drugs. Trial RegistrationClinicalTrials.gov NCT05072431; https://clinicaltrials.gov/ct2/show/NCT05072431